PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI BIAYA, KREDIBILITAS, DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT MENGGUNAKAN LPD MOBILE PADA NASABAH LPD DESA ADAT SIBETAN - Nyoman Ayu Wulan Trisna Dewi; Ni Gusti Ayu Putri Juliastini (Universitas Pendidikan Ganesha, 2021)
The purpose of this reseacrh is to determine the effect of perceived usefulness, perceived cost, credibility and ease of use on interest in using LPD Mobile. The type of research used is the type of quantitative research. This study uses primary data obtained by distributing questionnaires in the form of google form. The number of samples in this study were 100 people who had or used LPD Mobile. The results of this study indicate that the perception of usefulness has a positive and significant effect, the perception of cost has a positive and significant effect, credibility has a positive and significant effect and ease of use has a positive and significant effect simultaneously or jointly on the interest in using LPD Mobile on LPD customers in the Sibetan Traditional Village.